3CL hydrolase‐based multiepitope peptide vaccine against SARS‐CoV‐2 using immunoinformatics. Issue 10 (22nd May 2020) - Jakhar, Renu; Kaushik, Samander; Gakhar, Surendra K.
Abstract: The present study provides the first multiepitope vaccine construct using the 3CL hydrolase protein of SARS‐CoV‐2. The coronavirus 3CL hydrolase (Mpro) enzyme is essential for proteolytic maturation of the virus. This study was based on immunoinformatics and structural vaccinology strategies. The design of the multiepitope vaccine was built using helper T‐cell and cytotoxic T‐cell epitopes from the 3CL hydrolase protein along with an adjuvant to enhance immune response; these are joined to each other by short peptide linkers. The vaccine also carries potential B‐cell linear epitope regions, B‐cell discontinuous epitopes, and interferon‐γ‐inducing epitopes. Epitopes of the constructed multiepitope vaccine were found to be antigenic, nonallergic, nontoxic, and covering large human populations worldwide. The vaccine construct was modeled, validated, and refined by different programs to achieve a high‐quality three‐dimensional structure. The resulting high‐quality model was applied for conformational B‐cell epitope selection and docking analyses with toll‐like receptor‐3 for understanding the capability of the vaccine to elicit an immune response. In silico cloning and codon adaptation were also performed with the pET‐19b plasmid vector. The designed multiepitope peptide vaccine may prompt the development of a vaccine to control SARS‐CoV‐2 infection.